Meet Behind Mars - Simms, Renee (Book collections on Project MUSE., 2018)
Renee Simms's debut short story collection is a revealing look at how geography, memory, ancestry, and desire influence our personal relationships. In many of her stories, Simms exposes her own interest in issues concerning time and space. For example, in "Rebel Airplanes," an L.A. engineer works by day on city sewers and by night on R-C planes that she yearns to launch into the cosmos. The character-driven stories in Meet Behind Mars offer beautiful insight into the emotional lives of caretakers, auto workers, dancers, and pawn shop employees. In "High Country," a frustrated would-be novelist considers ditching her family in the middle of the desert. In "Dive," an adoptee returns to her adoptive home, still haunted by histories she does not know. Simms writes from the voice of women and girls who struggle under structural oppression and draws from the storytelling tradition best represented by writers like Edward P. Jones, whose characters have experiences that are specific to black Americans living in the late twentieth and twenty-first centuries